2020
DOI: 10.1016/j.jinf.2020.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of SARS-CoV-2 infection in staff working across different care homes: enhanced CoVID-19 outbreak investigations in London care Homes

Abstract: Background: Care homes have been disproportionately affected by the COVID-19 pandemic and continue to suffer lar ge outbreaks even when community infection rates are declining, thus representing important pockets of transmission. We assessed occupational risk factors for SARS-CoV-2 infection among staff in six care homes experiencing a COVID-19 outbreak during the peak of the pandemic in London, England. Methods: Care home staff were tested for SARS-COV-2 infection by RT-PCR and asked to report any symptoms, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 12 publications
3
83
0
Order By: Relevance
“…Congregate living or long-term care facilities often experience PPE shortages and chronic staffing shortages, and workers frequently lack formal training in infection prevention and control practices (6). HCP working in multiple long-term care facilities have been shown to be at higher risk for infection (7). The disparate exposure risks identified by MDH through HCP risk assessment and monitoring highlight a need for consistent PPE access and infection prevention and control training, especially in congregate living and long-term care settings.…”
Section: Discussionmentioning
confidence: 99%
“…Congregate living or long-term care facilities often experience PPE shortages and chronic staffing shortages, and workers frequently lack formal training in infection prevention and control practices (6). HCP working in multiple long-term care facilities have been shown to be at higher risk for infection (7). The disparate exposure risks identified by MDH through HCP risk assessment and monitoring highlight a need for consistent PPE access and infection prevention and control training, especially in congregate living and long-term care settings.…”
Section: Discussionmentioning
confidence: 99%
“…While the facility itself was able to implement strict mitigation policies, including restriction of visitors, staff were routinely coming in from the community. Furthermore, staff members might be more likely to present as asymptomatic cases than nursing home residents [ 13 , 33 , 34 ]. While analysis of staff transmission was beyond the scope of this study, staff infection was identified as a strong risk factor for resident mortality, alongside a temporal relationship that suggests residents were infected by staff [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, ref. 21 also shows that whole-genome sequencing of positive samples from residents and staff indicated cross-infection between residents and staff as well as multiple introductions of the virus into individual care homes. In a different congregate setting, movement of staff and residents across three affiliated homeless shelters likely contributed to outbreaks in each location ( 22 ).…”
Section: Covid-19 In Congregate Facilitiesmentioning
confidence: 95%
“…The CDC’s evaluation of the Kirkland, WA, outbreak pointed specifically to staff employed at multiple nursing homes as a factor in spreading the initial outbreak to additional homes ( 8 ). A study of four nursing homes in London ( 21 ) finds that 11% of staff worked in multiple homes, and these workers were 3 times as likely to be infected as workers in a single home. Further, ref.…”
Section: Covid-19 In Congregate Facilitiesmentioning
confidence: 99%